Analysis of Natural Resources Contracts Related to Article 33 Paragraph 2 and Paragraph 3 of the 1945 Constitution - Desafitri RB, Linda; Heliaantoro, Heliaantoro (Siber Journal of Advanced Multidisciplinary, 2024)
This article aims to identify challenges in the implementation of Article 33 of the 1945 Constitution in the context of the current global economy and offer a policy reform perspective to align natural resource management practices with the spirit of the constitution. Qualitative research methods are used by reviewing related scientific literature. The findings show a discrepancy between the principle of state control over natural resources and the practice of market liberalization. Key challenges include conflicts between state and market management, neglect of environmental conservation, and misalignment with global commitments to sustainability. To address these challenges, policy reforms are needed that integrate Article 33 principles in regulation, emphasize environmental sustainability, and be consistent with global commitments and public involvement in decision-making. This reform aims to ensure that the management of natural resources complies with the spirit of the constitution and provides maximum benefits for the welfare of the people and environmental sustainability. With these measures, Indonesia can more effectively align natural resource management practices with constitutional principles and achieve better welfare for the people and protect the environment.